Family Values in Tom Flynn’s Film Gifted - Muhammad Adrian Alfiansyah; Putri Widya Lestari; Sarah br Pardosi; Sri Jelita Savira; Syamsul Bahri (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This research analyzes family bonding values in Gifted written by Tom Flynn using Fritz Van Wel’s (1994) Family Bonding Theory. The objectives of this research are to identify the types of family bonding and explain how family values are represented through the emotional interactions among the characters in the movie. This research uses a qualitative descriptive method because the study focuses on dialogues, scenes, and emotional relationships portrayed in the movie. The primary data of this research are dialogues and scenes related to family relationships between Frank Adler, Mary Adler, and Evelyn Adler. The researcher collected the data by watching the movie repeatedly, identifying important scenes, and classifying the data according to Van Wel's idea, it includes intimacy, love, closeness, trust, commitment, attachment, and interdependence. The result of this research show that all aspects of family bonding are represented in the movie. Attachment becomes the most dominant aspect because the story mainly focuses on emotional protection, affection, and support between Frank and Mary. In addition, the movie also portrays commitment, interdependence, closeness, trust, intimacy, and love through parenting conflicts, sacrifice, communication, and emotional struggles among the characters. The researcher concludes that family relationships are formed not only through biological connections but also through emotional care, responsibility, and unconditional love. Therefore, Gifted reflects the importance of strong emotional relationships in maintaining family harmony and emotional well-being.